Analisis Materi Video Hallo Deutschschule sebagai Bahan Ajar Keterampilan Berbicara Bahasa Jerman Kelas XI - Jules, Jemima; Ari Pujosusanto (LATERNE, 2025)
Hallo Deutschschule is a channel on Youtube that contains German learning videos. The videos have material that has the potential to help student learning tema Essen und Trinken speaking skills. This study aims to answer the formulation of the problem, namely to determine the suitability of the video material Hallo Deutschschule tema Essen und Trinken as teaching materials for Class XI German speaking skills. The method used in this study is to refer to the video record on the Channel Hallo Deutschschule which is the source of data in this study. Data is in the form of words and sentences contained in the video. Data collection technique begins with video transcription writing. The data analysis technique begins with data reduction, namely sorting out the points that correspond to the theme of Essen und Trinken. At the stage of presentation and conclusion, the data are presented in tables, compared, and analyzed for suitability. The next data is calculated to produce the percentage of conformity results obtained by 88% Hallo Deutschschule video material in accordance with the curriculum material 2013 theme Essen und Trinken.